2014
DOI: 10.12968/joan.2014.3.3.134
|View full text |Cite
|
Sign up to set email alerts
|

Ageing, anxiety and appearance: exploring the body image of women in midlife

Abstract: Most research surrounding body image has focused on young women, yet appearance dissatisfaction and eating disorders are on the rise in middle-aged and older women. In this article, PhD researcher Helena Lewis-Smith provides aesthetic nurses with some insight into the factors contributing to these issues, and discusses novel methods for promoting positive body image within this group

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The relationship between older women's body image and the ageing process is multi-faceted and dynamic. Women aged 35 and over are not immune to concerns about ageing; societal pressure, media images and attitudes of friends and family all contribute to worry and dissatisfaction about key areas of appearance, including the face (Lewis-Smith, 2014). At the same time, there is also evidence that older women self-objectify to a lesser degree than do younger women, although this effect possibly occurs later than 65 years of age (Tiggemann, 2001;2004).…”
mentioning
confidence: 99%
“…The relationship between older women's body image and the ageing process is multi-faceted and dynamic. Women aged 35 and over are not immune to concerns about ageing; societal pressure, media images and attitudes of friends and family all contribute to worry and dissatisfaction about key areas of appearance, including the face (Lewis-Smith, 2014). At the same time, there is also evidence that older women self-objectify to a lesser degree than do younger women, although this effect possibly occurs later than 65 years of age (Tiggemann, 2001;2004).…”
mentioning
confidence: 99%
“…Although there is literature that reports women experience anxiety regarding their aging appearance and weight (Jankowski et al., 2016), older Brazilian women in the study acknowledged that change is inevitable and embraced the changes that came with the aging process and as such described their experience as Aging with Grace. Research about older women indicates that many women feel conflicting pressures to resist aging and not accept the physical changes that result from aging (Jankowski et al., 2016; Lewis-Smith, 2014) due to the negative stereotypes associated with aging. A study by Cordeiro and Pereira (2016) explored older Brazilian women’s perceptions of their aging body and found that the Brazilian culture rejected the physical signs of aging and created preoccupation with physical appearance and cosmetic services to combat aging appearance (Cordeiro & Pereira, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Women in my study discussed the importance of challenging the sociocultural norms and discourse on aging regarding their aging appearance. However, research regarding older women indicates that many women feel conflicting pressures to resist aging and not accept the physical changes that result from aging (Jankowski et al, 2016;Lewis-Smith, 2014) due to the negative stereotypes associated with aging. Women in my study emphasized that by accepting the physical changes that result from aging, they felt at peace and relaxed and not imprisoned by society's ideology of maintaining a youthful appearance.…”
Section: Lived Body: Aging With Gracementioning
confidence: 99%